2–forms (rotations)#

by Stéphane Haussler

This article investigates the exterior derivative of rotations expressed in differential form. We employ the Cartan-Hodge formalism within the context of Minkowski spacetime. Following the systematic calculations presented in this article, I demonstrate in Of Maxwell Equations and Rotations that a twist in spacetime leads to the equations governing electromagnetism.

While the concept might not be entirely novel, I have not yet encountered some of my observations elsewhere. If you are aware of relevant references, feel free to open an issue and I will include them. I you identify any errors, you can either open an issue, or directly submit corrections via a merge request to my GitHub repository: Theoretical Universe.

Rotations#

Rotations in spacetime can occur in six independent planes. Any rotation can be decomposed into a linear combination of basis rotations within each plane:

\[\begin{split}R^{♯♯} = \begin{bmatrix} Q^x \; ∂_t ∧ ∂_x \\ Q^y \; ∂_t ∧ ∂_y \\ Q^z \; ∂_t ∧ ∂_z \\ R^x \; ∂_y ∧ ∂_z \\ R^y \; ∂_z ∧ ∂_x \\ R^z \; ∂_x ∧ ∂_y \\ \end{bmatrix}\end{split}\]

The generic rotation above is doubly contravariant, given in terms of the wedge product \(∧\) of vectors corresponding to our physical understanding of space (and time). By fully flattening, we obtain the associated doubly covariant differential 2-form representative of the rotation:

\[\begin{split}R^{♭♭} = \left[ \begin{aligned} - & Q^x \; dt ∧ dx \\ - & Q^y \; dt ∧ dy \\ - & Q^z \; dt ∧ dz \\ & R^x \; dy ∧ dz \\ & R^y \; dz ∧ dx \\ & R^z \; dx ∧ dy \\ \end{aligned} \right]\end{split}\]

\(⋆ R^{♭♭}\)#

Applying the Hodge star to the rotation 2-form, we obtain:

\[\begin{split}⋆ R^{♭♭} = \left[ \begin{aligned} & Q^x \; dy ∧ dz \\ & Q^y \; dz ∧ dx \\ & Q^z \; dx ∧ dy \\ & R^x \; dt ∧ dx \\ & R^y \; dt ∧ dy \\ & R^z \; dt ∧ dz \\ \end{aligned} \right]\end{split}\]

\(d R^{♭♭}\)#

Apply the exterior derivative to the rotation 2-form, we obtain:

\[\begin{split}dR^{♭♭} = \left[ \begin{alignedat}{5} (& & + ∂_x R^x & + ∂_y R^y & + ∂_z R^z &\:) \; dx^x ∧ dx^y ∧ dx^z \\ (& + ∂_t R^x & & + ∂_y Q^z & - ∂_z Q^y &\:) \; dx^t ∧ dx^y ∧ dx^z \\ (& + ∂_t R^y & - ∂_x Q^z & & + ∂_z Q^x &\:) \; dx^t ∧ dx^z ∧ dx^x \\ (& + ∂_t R^z & + ∂_x Q^y & - ∂_y Q^x & &\:) \; dx^t ∧ dx^x ∧ dx^y \\ \end{alignedat} \right]\end{split}\]

\(d⋆ R^{♭♭}\)#

Applying in sequence the exterior derivative and the Hodge star operator to the rotation 2-form, we obtain:

\[\begin{split}d( ⋆ R^{♭♭} ) = \left[ \begin{alignedat}{5} (& & + ∂_x Q^x & + ∂_y Q^y & + ∂_z Q^z &\:) \; dx ∧ dy ∧ dz \\ (& + ∂_t Q^x & & - ∂_y R^z & + ∂_z R^y &\:) \; dt ∧ dy ∧ dz \\ (& + ∂_t Q^y & + ∂_x R^z & & - ∂_z R^x &\:) \; dt ∧ dz ∧ dx \\ (& + ∂_t Q^z & - ∂_x R^y & + ∂_y R^x & &\:) \; dt ∧ dx ∧ dy \\ \end{alignedat} \right]\end{split}\]

\(⋆d R^{♭♭}\)#

Applying in sequence the Hodge star and the exterior derivative operator \(d\) to the rotation 2-form, we obtain:

\[\begin{split}⋆ dR^{♭♭} = \left[ \begin{alignedat}{5} (& & - ∂_x R^x & - ∂_y R^y & - ∂_z R^z &\:) \; dt \\ (& - ∂_t R^x & & - ∂_y Q^z & + ∂_z Q^y &\:) \; dx \\ (& - ∂_t R^y & + ∂_x Q^z & & - ∂_z Q^x &\:) \; dy \\ (& - ∂_t R^z & - ∂_x Q^y & + ∂_y Q^x & &\:) \; dz \\ \end{alignedat} \right]\end{split}\]

\(⋆d⋆ R^{♭♭}\)#

Applying the Hodge star to \(d⋆R^{♭♭}\), we obtain:

\[\begin{split}⋆d⋆R^{♭♭} = \left[ \begin{alignedat}{5} (& & + ∂_x Q^x & + ∂_y Q^y & + ∂_z Q^z &\:) \; dt \\ (& + ∂_t Q^x & & - ∂_y R^z & + ∂_z R^y &\:) \; dx \\ (& + ∂_t Q^y & + ∂_x R^z & & - ∂_z R^x &\:) \; dy \\ (& + ∂_t Q^z & - ∂_x R^y & + ∂_y R^x & &\:) \; dz \\ \end{alignedat} \right]\end{split}\]

\(d⋆d R^{♭♭}\)#

Applying the exterior derivative to \(⋆d R^{♭♭}\), we obtain:

\[\begin{split}d⋆d R^{♭♭} &= \left[ \begin{alignedat}{4} & ( - ∂_t^2 R^x & + ∂_x^2 R^x & & & ) \; dt ∧ dx \\ & ( - ∂_t^2 R^y & & + ∂_y^2 R^y & & ) \; dt ∧ dy \\ & ( - ∂_t^2 R^z & & & + ∂_z^2 R^z & ) \; dt ∧ dz \\ \end{alignedat} \right] \\[2mm] &+ \left[ \begin{alignedat}{4} & ( & + ∂_y^2 Q^x & + ∂_z^2 Q^x & ) \; dy ∧ dz \\ & (+ ∂_x^2 Q^y & & + ∂_z^2 Q^y & ) \; dz ∧ dx \\ & (+ ∂_x^2 Q^z & + ∂_y^2 Q^z & & ) \; dx ∧ dy \\ \end{alignedat} \right] \\[2mm] &+ \left[ \begin{alignedat}{4} & ( & - ∂_t ∂_y Q^z & + ∂_t ∂_z Q^y & ) \; dt ∧ dx \\ & ( + ∂_t ∂_x Q^z & & - ∂_t ∂_z Q^x & ) \; dt ∧ dy \\ & ( - ∂_t ∂_x Q^y & + ∂_t ∂_y Q^x & & ) \; dt ∧ dz \\ \end{alignedat} \right] \\[2mm] &+ \left[ \begin{alignedat}{4} & ( & - ∂_z ∂_x Q^y & - ∂_x ∂_y Q^y & ) \; dy ∧ dz \\ & ( - ∂_y ∂_z Q^z & & - ∂_x ∂_y Q^x & ) \; dz ∧ dx \\ & ( - ∂_y ∂_z Q^y & - ∂_z ∂_x Q^x & & ) \; dx ∧ dy \\ \end{alignedat} \right] \\[2mm] &+ \left[ \begin{alignedat}{4} & ( & + ∂_x ∂_y R^y & + ∂_x ∂_z R^z & ) \; dt ∧ dx \\ & ( + ∂_y ∂_x R^x & & + ∂_y ∂_z R^z & ) \; dt ∧ dy \\ & ( + ∂_z ∂_x R^x & + ∂_z ∂_y R^y & & ) \; dt ∧ dz \\ \end{alignedat} \right] \\[2mm] &+ \left[ \begin{alignedat}{4} & ( & - ∂_t ∂_y R^z & + ∂_t ∂_z R^y & ) \; dy ∧ dz \\ & ( + ∂_t ∂_x R^z & & - ∂_t ∂_z R^x & ) \; dz ∧ dx \\ & ( - ∂_t ∂_x R^y & + ∂_t ∂_y R^x & & ) \; dx ∧ dy \\ \end{alignedat} \right] \\[2mm]\end{split}\]

\(d⋆d⋆R^{♭♭}\)#

Applying the exterior derivative to \(⋆d⋆R^{♭♭}\), we obtain:

\[\begin{split}d⋆d⋆ R^{♭♭} &= \left[ \begin{alignedat}{4} & ( + ∂_t^2 Q^x & - ∂_x^2 Q^x & & & ) \; dt ∧ dx \\ & ( + ∂_t^2 Q^y & & - ∂_y^2 Q^y & & ) \; dt ∧ dy \\ & ( + ∂_t^2 Q^z & & & - ∂_z^2 Q^z & ) \; dt ∧ dx \\ \end{alignedat} \right] \\[2mm] &+ \left[ \begin{alignedat}{4} & ( & + ∂_y^2 R^x & + ∂_z^2 R^x & ) \; dy ∧ dz \\ & ( + ∂_x^2 R^y & & + ∂_z^2 R^y & ) \; dz ∧ dx \\ & ( + ∂_x^2 R^z & + ∂_y^2 R^z & & ) \; dx ∧ dy \\ \end{alignedat} \right] \\[2mm] &+ \left[ \begin{alignedat}{4} & ( & - ∂_x ∂_y Q^y & - ∂_z ∂_x Q^z & ) \; dt ∧ dx \\ & ( - ∂_x ∂_y Q^x & & - ∂_y ∂_z Q^z & ) \; dt ∧ dy \\ & ( - ∂_z ∂_x Q^x & - ∂_z ∂_y Q^y & - & ) \; dt ∧ dx \\ \end{alignedat} \right] \\[2mm] &+ \left[ \begin{alignedat}{4} & ( & + ∂_t ∂_y Q^z & - ∂_t ∂_z Q^y & ) \; dy ∧ dz \\ & ( - ∂_t ∂_x Q^z & & + ∂_t ∂_z Q^x & ) \; dz ∧ dx \\ & ( + ∂_t ∂_x Q^y & - ∂_t ∂_y Q^x & & ) \; dx ∧ dy \\ \end{alignedat} \right] \\[2mm] &+ \left[ \begin{alignedat}{4} & ( & - ∂_t ∂_y R^z & + ∂_t ∂_z R^y & ) \; dt ∧ dx \\ & ( + ∂_t ∂_x R^z & & - ∂_t ∂_z R^x & ) \; dt ∧ dy \\ & ( - ∂_t ∂_x R^y & + ∂_t ∂_y R^x & & ) \; dt ∧ dz \\ \end{alignedat} \right] \\[2mm] &+ \left[ \begin{alignedat}{4} & ( & - ∂_x ∂_y R^y & - ∂_x ∂_z R^z & ) \; dy ∧ dz \\ & ( - ∂_y ∂_x R^x & & - ∂_y ∂_z R^z & ) \; dz ∧ dx \\ & ( - ∂_z ∂_x R^x & - ∂_z ∂_y R^y & & ) \; dx ∧ dy \\ \end{alignedat} \right]\end{split}\]

\(⋆d⋆d R^{♭♭}\)#

\[\begin{split}⋆d⋆d R^{♭♭} &= \left[ \begin{alignedat}{4} & ( + ∂_t^2 R^x & - ∂_x^2 R^x & & & ) \; dy ∧ dz \\ & ( + ∂_t^2 R^y & & - ∂_y^2 R^y & & ) \; dy ∧ dx \\ & ( + ∂_t^2 R^z & & & - ∂_z^2 R^z & ) \; dy ∧ dy \\ \end{alignedat} \right] \\[2mm] &+ \left[ \begin{alignedat}{4} & ( & + ∂_y^2 Q^x & + ∂_z^2 Q^x & ) \; dt ∧ dx \\ & ( + ∂_x^2 Q^y & & + ∂_z^2 Q^y & ) \; dt ∧ dy \\ & ( + ∂_x^2 Q^z & + ∂_y^2 Q^z & & ) \; dt ∧ dz \\ \end{alignedat} \right] \\[2mm] &+ \left[ \begin{alignedat}{4} & ( & - ∂_x ∂_y Q^y & - ∂_z ∂_x Q^z & ) \; dt ∧ dx \\ & ( - ∂_x ∂_y Q^x & & - ∂_y ∂_z Q^z & ) \; dt ∧ dy \\ & ( - ∂_z ∂_x Q^x & - ∂_y ∂_z Q^y & & ) \; dt ∧ dz \\ \end{alignedat} \right] \\[2mm] &+ \left[ \begin{alignedat}{4} & ( & + ∂_t ∂_y Q^z & - ∂_t ∂_z Q^y & ) \; dy ∧ dz \\ & ( - ∂_t ∂_x Q^z & & + ∂_t ∂_z Q^x & ) \; dy ∧ dx \\ & ( + ∂_t ∂_x Q^y & - ∂_t ∂_y Q^x & & ) \; dy ∧ dy \\ \end{alignedat} \right] \\[2mm] &+ \left[ \begin{alignedat}{4} & ( & - ∂_t ∂_y R^z & + ∂_t ∂_z R^y & ) \; dt ∧ dx \\ & ( + ∂_t ∂_x R^z & & - ∂_t ∂_z R^x & ) \; dt ∧ dy \\ & ( - ∂_t ∂_x R^y & + ∂_t ∂_y R^x & & ) \; dt ∧ dz \\ \end{alignedat} \right] \\[2mm] &+ \left[ \begin{alignedat}{4} & ( & - ∂_x ∂_y R^y & - ∂_x ∂_z R^z & ) \; dy ∧ dz \\ & ( - ∂_y ∂_x R^x & & - ∂_y ∂_z R^z & ) \; dz ∧ dx \\ & ( - ∂_z ∂_x R^x & - ∂_z ∂_y R^y & & ) \; dx ∧ dy \\ \end{alignedat} \right]\end{split}\]

\(d⋆d⋆ - ⋆d⋆d\)#

\[\begin{split}(d⋆d⋆ - ⋆d⋆d) \left[ \begin{aligned} - & Q^x \; dt ∧ dx \\ - & Q^y \; dt ∧ dy \\ - & Q^z \; dt ∧ dz \\ & R^x \; dy ∧ dz \\ & R^y \; dz ∧ dx \\ & R^z \; dx ∧ dy \\ \end{aligned} \right] &= \left[ \begin{alignedat}{5} & ( + ∂_t^2 Q^x & - ∂_x^2 Q^x & - ∂_y^2 Q^x & - ∂_z^2 Q^x & \: ) \; dt∧dx \\ & ( + ∂_t^2 Q^y & - ∂_x^2 Q^y & - ∂_y^2 Q^y & - ∂_z^2 Q^y & \: ) \; dt∧dy \\ & ( + ∂_t^2 Q^z & - ∂_x^2 Q^z & - ∂_y^2 Q^z & - ∂_z^2 Q^z & \: ) \; dt∧dz \\ & ( - ∂_t^2 R^x & + ∂_x^2 R^x & + ∂_y^2 R^x & + ∂_z^2 R^x & \: ) \; dy∧dz \\ & ( - ∂_t^2 R^y & + ∂_x^2 R^y & + ∂_y^2 R^y & + ∂_z^2 R^y & \: ) \; dz∧dx \\ & ( - ∂_t^2 R^z & + ∂_x^2 R^z & + ∂_y^2 R^z & + ∂_z^2 R^z & \: ) \; dx∧dy \\ \end{alignedat} \right]\end{split}\]